2020
DOI: 10.1002/chem.202001295
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Make a Chain: A Catenated Bismuth Compound

Abstract: Catenation is common for the light main‐group elements whereas it is rare for the heavy elements. Herein, we report the first example of a neutral molecule containing a Bi4 chain. It is prepared in a one‐step reaction between bismuth trichloride and bis(diisopropylphosphino)amine in methanol suspension. The same reaction carried out in dichloromethane gives quite different products. All products have been characterized spectroscopically and using single‐crystal X‐ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“…Compound 4‐Al crystallizes in the triclinic space group P 1 ${\bar{1}}$ (Figure 1—right), revealing the structure of an unprecedented heptanuclear organometallic bismuth complex cation. While a range of oligonuclear bismuth‐containing clusters [28] and ligand‐stabilized chains of up to four bismuth atoms have been reported, [29] compound 4‐Al is best described as a molecular complex, albeit two Bi→Bi donor/acceptor interactions are present (see below). The global structure of complex 4‐Al resembles that of an open barrel and is analyzed using the connectivity scheme in Scheme 1b.…”
Section: Methodsmentioning
confidence: 99%
“…Compound 4‐Al crystallizes in the triclinic space group P 1 ${\bar{1}}$ (Figure 1—right), revealing the structure of an unprecedented heptanuclear organometallic bismuth complex cation. While a range of oligonuclear bismuth‐containing clusters [28] and ligand‐stabilized chains of up to four bismuth atoms have been reported, [29] compound 4‐Al is best described as a molecular complex, albeit two Bi→Bi donor/acceptor interactions are present (see below). The global structure of complex 4‐Al resembles that of an open barrel and is analyzed using the connectivity scheme in Scheme 1b.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper, we reported the synthesis of a novel catenated bismuth compound 6. 7 The reaction involved in this synthesis occurred in methanol, and 6 was found to be stabilized by the presence of two iso-propyl PNP ligands bridging pairs of bismuth atoms. Elucidation of the mechanism by which this compound formed is central to the studies presented here, with the focus on the formation of [1-(OCH 3 ) 2 ] + .…”
Section: Coupled Reactions In the Assembly Of A Catenated Bismuth Com...mentioning
confidence: 99%
“…We recently investigated the reactions of 1(H) with BiCl 3 and found that they were solvent dependent. 7 In one case, the addition of a dichloromethane (DCM) solution of 1(H) to a suspension of BiCl 3 in the same solvent gave compound 4 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Analyse offenbarte die präzedenzlose Molekülstruktur eines siebenkernigen metallorganischen Bismut-Komplexkations. Während eine Reihe oligonuklearer Bismut-haltiger Cluster [28] und Ligand-stabilisierte Ketten von bis zu vier Bismutatomen berichtet wurden, [29] Die flachen Energieprofile, die für einige Schritte von BiÀ C-Bindungsbrüchen berichtet wurden, [12][13][14]21,30] [21] polare Reaktionspfade in der Anwesenheit von [BiMe 2 (SbF 6 )] plausibel erscheinen. Zugleich wurden allerdings bereitwillig verlaufende homolytische Bindungsdissoziationen von Bismutspecies beschrieben, [31][32][33][34]…”
unclassified